2022
DOI: 10.32535/jcda.v5i2.1492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Market Orientation, Learning Orientation, and Innovation Capabilities and Their Impact on Competitive Advantage and Company Performance

Abstract: To meet the needs of heterogeneous consumers, companies must be market-oriented and innovate to advance company performance. This research will analyze the influence of market orientation, learning orientation, innovation capabilities, and their impact on competitive advantage and company performance in Ngelorejo bamboo craft center, Gunung Kidul district, Indonesia. In the collection of data, this study used questionnaires with the number of respondents as many as 88 respondents bamboo artisans. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Increased innovation has an impact on improving the performance of MSMEs, as shown by an increase in good financial performance by achieving profits and increasing business capital in the last 3 years. The results of this study develop previous empirical studies conducted by Wahyuni and Giantari (2019), Yang et al (2022) and Laksana et al (2022) that learning orientation is a good predictor for increasing innovation and the results of this study are in accordance with the study presented by Eris et al (2012), Saunila and Ukko (2014), Rosli and Sidek (2013), Serna et al (2016), Nybakk (2012), Zhang and Chen (2014) concluded that innovation capability has an influence on MSME performance.…”
Section: Mediation Role Of Innovation Capabilitysupporting
confidence: 92%
See 2 more Smart Citations
“…Increased innovation has an impact on improving the performance of MSMEs, as shown by an increase in good financial performance by achieving profits and increasing business capital in the last 3 years. The results of this study develop previous empirical studies conducted by Wahyuni and Giantari (2019), Yang et al (2022) and Laksana et al (2022) that learning orientation is a good predictor for increasing innovation and the results of this study are in accordance with the study presented by Eris et al (2012), Saunila and Ukko (2014), Rosli and Sidek (2013), Serna et al (2016), Nybakk (2012), Zhang and Chen (2014) concluded that innovation capability has an influence on MSME performance.…”
Section: Mediation Role Of Innovation Capabilitysupporting
confidence: 92%
“…The results of this study are in accordance with the opinion expressed by Baker and Sinkula (2002), who stated that learning orientation prepares companies to enter a stage where they will commit to systematically challenging the fundamental beliefs and practices that define their innovation process and support the results of the study. Previous empirical research conducted by Wahyuni and Giantari (2019), Yang et al (2022) and Laksana et al (2022) stated that learning orientation is a good predictor of increasing innovation.…”
Section: Learning Orientation Influences Innovation Capabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Expertise is certainly needed in a company's strategy process, decision-making, strategy implementation, and strategy evaluation process. So that it will bring up opportunities and threats for companies that make companies to be swift and precise in determining steps or decisions (Laksana, Apriliado, & Kusmantini, 2022). Therefore, those who are geared with better compatibilities in expertise, experience, knowledge, and ability can generate more inputs for problems and firm performance handling (Hillman & Dalziel, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Small and Medium Enterprises (SMEs) have a substantial and noteworthy part in the economy of Indonesia. The presence of SMEs is a fundamental aspect of the Indonesian economy (Laksana, Apriliado, & Kusmantini, 2022). Like many other emerging economies, small and medium companies (SMEs) play a significant role in driving the economic progress of Indonesia.…”
Section: Introductionmentioning
confidence: 99%